(untitled) (Research, Society and Development, 2023)
Introduction: Congenital syphilis (CS) is an important public health problem in Brazil. Failure to treat sexual partners is one of the main factors that make it difficult to control CS and continues to be a challenge for health professionals (Rocha, et al., 2019). The partner’s poor adherence contributes to the exponential growth in the number of infections and children affected with CS in recent years, but such data are still limited. Objective: The objective was to conduct a survey to evaluate the treatment of partners of puerperal women who had syphilis during pregnancy and whose children were diagnosed with congenital syphilis. Methods: Cross-sectional, retrospective and analytical study carried out in a Philanthropic Maternity Hospital in Aracaju SE, from 2010 to 2020. Data were collected from the paper records of patients with congenital syphilis, at the newborn follow-up clinic. Results: With regard to maternal treatment, 5.4% of the women were not treated, 15.8% were inadequately treated and 78.8% were adequately treated. Regarding paternal treatment, 30.4% of the men did not, 29.6% did it inappropriately and 40.1% were treated properly. Furthermore, 25.3% had 1 child with the disease in another pregnancy and 6.8% had 2 or more children with syphilis. The incidence of abortions was zero for 75.8% of women. Conclusion: Through this vision, it is concluded that the treatment of the partners of seropositive women during pregnancy is still neglected in Brazil, since approximately 30% of the men in this analysis were not treated for syphilis and 30% were treated inappropriately.